2016
DOI: 10.1002/adfm.201601557
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Controlled Hydration Water for Performance Improvement of Organic–Inorganic Perovskite Solar Cells

Abstract: Recently, intensive studies on the role of water molecule in the formation of organic–inorganic perovskite film have been reported. However, not only the contradictive phenomena but also the complex processing technique has hindered the widespread use of water molecule in perovskite preparation. Here the hydration water is introduced into the precursors instead of water. By precisely controlling the content of hydration water, a smoother and more uniform perovskite film is obtained through a simple one‐step sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 29 publications
0
59
0
Order By: Relevance
“…[21][22][23][24][25][26][27] The second recipe is based on the solvent engineering technique introduced by Jeon et al in 2014. The first recipe is based on a lead acetate trihydrate (PbAc 2 ·3H 2 O) precursor and has attracted significant attention for application in inverted architecture solar cells since its introduction by Zhang and co-workers.…”
Section: Photovoltaic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27] The second recipe is based on the solvent engineering technique introduced by Jeon et al in 2014. The first recipe is based on a lead acetate trihydrate (PbAc 2 ·3H 2 O) precursor and has attracted significant attention for application in inverted architecture solar cells since its introduction by Zhang and co-workers.…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…[31][32][33] Conversely, the SEM cross-section of the sol-eng film shows that the film consists of multiple grains which are larger at the interface with PEDOT:PSS and smaller at the film surface. [23,26,47] Choosing these two recipes allows us to compare the rate of oxygen induced degradation of perovskite films with few defects and large grains protruding throughout the film thickness to that of a film with higher defect density and small and irregular grains. Recently, it has been shown that reduced PL originates from recombination centers located mainly at the surface and grain boundaries of the perovskite crystals.…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…The authors found an optimum by using PbAc 2 × 1.5H 2 O, which resulted in the highest PCEs. [44] Several studies already showed that exposure of the films to ambient conditions can have a positive effect on perovskite film formation, [45] i.e., it was shown to trigger the crystallization [46] or partly dissolve the reactant species and accelerate mass transport within the film. [3] In a recent study, Giesbrecht et al used lead acetate as the precursor for the crystallization of methylammonium lead bromide (MAPbBr 3 ) perovskite films.…”
Section: Crystallization From Lead-acetate Precursorsmentioning
confidence: 99%
“…[11][12][13] Among the previous research works, hybrid lead halide perovskites have been used in many fields, such as solar cells, 1,2,5,8,9,14 light-emitting diodes, [15][16][17][18][19] sensitive photodetectors, [20][21][22] and lasers. 4,23,24 It is necessary to mention about the photovoltaic applications, which is a very hot research topic recently, that the latest reported power conversion efficiency has been increased remarkably from the original 3.8% (Ref.…”
mentioning
confidence: 99%